Effectiveness of pre-Omicron COVID-19 mRNA vaccines against hospitalizations in infection-naïve children: a case-control study - Chang, Lung; Huang, Ching-Ying; Chiu, Nan-Chang; Wang, Jin-Yuan; Chi, Hsin; Huang, Tsung-Ning Daniel (Frontiers in Pediatrics, 2024)
This case-control study spanned from July 2022 to September 2023, focusing on the pre-Omicron COVID-19 mRNA vaccines effectiveness against Omicron variant in children without prior SARS-CoV-2 exposure. We reported that pre-Omicron COVID-19 mRNA vaccines significantly reduced Omicron-induced hospitalizations in infection-naïve Taiwanese children. Our study also highlighted the socio-economic factors influencing COVID-19 vulnerability among children population.